(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2022)
The paper’s aim is to show how the famine crisis was dealt with in Parma in the period 1258-1259. Thanks to the chronicles and a fortunate series of coeval Statuti, it is possible to observe how the regime of lordship led by the miles Giberto da Gente faced the famine caused by the Samalas eruption, not only by reinforcing measures already present in Parma but also by introducing innovative procedures and magistrates. In an increasingly connected Italian context, it will be seen how the famine determined, through precise political and economic choices made by da Gente, the outcome of the first lordship of Parma.